The Relationship between Perceptions of the Availability of Hospital Facilities and Infrastructure to the Level of Fire Disaster Preparedness among Clinical Clerkship Students in Zainoel Abidin Hospital - T Husni TR; Yulia Agustina; Taufik Suryadi (International Journal of Disaster Management, 2021)
Clinical clerkship students are one of the communities who are always in the hospital environment and have been provided with fire disaster management materials through training and simulations. The hospital has provided complete fire disaster management facilities and infrastructure. However, the problem is that there is no information about clinical clerkship student preparedness for fire disasters in hospitals. The purpose of this study is to determine the relationship between perceptions of the availability of hospital facilities and infrastructure to the level of fire disaster preparedness among clinical clerkship students in the Zainoel Abidin Hospital. This study used an analytical method with a cross-sectional design. The sample of this study was the clinical clerkship students of the Faculty of Medicine, Syiah Kuala University, who were taken by proportional stratified random sampling, totaling 117 people. The data was collected using an online questionnaire that has been tested for its validity and reliability. Data analysis was performed univariate and bivariate using the chi-square test. The results showed that the clinical clerkship student had a good perception regarding facilities and infrastructure in the hospital (68.4%), while the attitude of preparedness to face fire disasters in the hospital showed a high level (80.3%). The Chi-square test results showed that there was a significant relationship between the clinical clerkship student perception regarding facilities and infrastructure in hospitals and fire disaster preparedness (p = 0,000). The conclusion of this study showed that the good perceptions of clinical clerkship students about the availability of fire disaster management facilities and infrastructure increase fire disaster preparedness in the hospital. This study recommends the importance of training and fire disaster management simulation to be continuously carried out on clinical clerkship students to improve the quality of disaster preparedness communities.